Dobutamine 3D strain in the left anterior descending subtended ventricular territory: evidence for relationship with the respective velocity flow reserve. (4th February 2022) - Armenis, I; Armenis, I; Demerouti, E; Demerouti, E; Athanassopoulos, GD; Motsi, A; Athanassopoulos, GD
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction Three dimensional speckle tracking imaging (3DST), provides an evolving means to interrogate left ventricular (LV) function. However, its clinical application still remains limited. Purpose Purpose of the study was to interrogate the relationship between regional deformation by 3DST in left anterior descending artery (LAD) subtended territory and the respective coronary flow reserve (CFR). Methods: Fifty patients aged 63 ± 6 years with chronic coronary syndromes were studied. Patients had no evidence of dobutamine (DOB) induced ischemia in LAD territory. Distal LAD CFR was estimated by adenosine Doppler echo (140mg/kg/min). 3DST derived integral strain (IS) and respective components (longitudinal -LS, circumferential –CS, radial -RS) were estimated by a full volume sweep (3.5 MHz sector probe) at >20 volumes/sec. A 16 LV sectors (sc) polar map was provided (Artida, Toshiba) with 10/16 sectors (sc) analysed, 6 sc being the conventional LAD territory (sc: 3, 4, 5, 6, 7, 8) and another 4 sc being adjacent ones (sc: 1, 2, 9, 10). 3D datasets acquired at rest (R) and low dose DOB (20mg/kg/min). LV mass was automatically measured from volumetric data sets and its variability during cardiac cycle was considered as an index of coherence for true LV borders recognition. Results CFR was >2 in all pts (range 2.0-4.2, 2.74 + 0.46). Mean variability of LV mass between R and DOB was 0.044 (range: -0.090-0.008, p = ns). 3DST strain was related with LAD CFR as follows: 1.For IS: at R: sc1: r = 0.38, p = 0.023, sc3: r = 0.44, p = 0.006, sc5: r = 0.35, p = 0.03, sc9: r = 0.50, p = 0.002. At DOB: sc7: r = 0.31, p = 0.05. 2.For LS: at R: sc5: r=-0.40, p = 0.01. 3.For CS: at R: sc5: r=-0.33, p = 0.02, sc5: r=-0.46, p = 0.004. 4.For RS: at R: sc9: r=-0.38, p = 0.08. The % changes of regional IS post DOB compared to R were also related with CFR LAD in the sectors sc1 and sc3 (r = 0.34, p = 0.05, and p = 0.40, p = 0.002 respectively). Conclusion: 3DST derived LV deformation indices in the LAD territory are related with the respective CFR. LV regional integral strain has a stronger relationship with LAD CFR when compared to the partial vectors. The 3DST derived deformation indices seem sensitive enough to reproduce the flow function relationship in the LAD territory. Thus, potential applicability has to be supported.